A Study on the Role of Costumes in Driving Narrative Progression in Cinematic Character Construction - Liu, Yi (Transactions on Social Science, Education and Humanities Research, 2025)
In cinematic storytelling, costumes not only serve superficial functional purposes but also act as critical visual language that drives narrative progression and character development. With the growing intersection of visual culture and identity politics, costume design in film has evolved into a mediating symbol connecting characters’ inner worlds with external contexts. This study examines two culturally distinct films - In the Mood for Love (2000) and The Devil Wears Prada (2006) - to investigate how costumes function in externalizing psychological states, advancing plotlines, and conveying cultural symbolism, thereby revealing their narrative significance in character construction. The research methodology combines textual with visual semiotic analysis, conducting a comparative study of how costumes interact with narrative pacing, emotional dynamics, and social contexts in both films. Key findings demonstrate that Maggie Cheung’s cheongsam dresses in In the Mood for Love not only facilitate the gradual evolution of her relationship with Chow Mo-wan but also visually manifest the tension between emotional repression and traditional ethics. Conversely, Anne Hathaway’s wardrobe transformation in The Devil Wears Prada systematically maps her identity shift from an “outsider” to a corporate elite, mirroring her reconstructed value system. The research concludes that cinematic costumes serve dual narrative purposes: they provide visual cues for plot advancement while simultaneously externalizing characters’ psychological growth and sociocultural identity transitions.